2014
DOI: 10.1186/1678-9199-20-49
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hemolytic activity induced by the aqueous extract of the Mexican fire coral Millepora complanata

Abstract: BackgroundMillepora complanata is a plate-like fire coral common throughout the Caribbean. Contact with this species usually provokes burning pain, erythema and urticariform lesions. Our previous study suggested that the aqueous extract of M. complanata contains non-protein hemolysins that are soluble in water and ethanol. In general, the local damage induced by cnidarian venoms has been associated with hemolysins. The characterization of the effects of these components is important for the understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…The results obtained in this study showed that rat erythrocytes were more sensitive to P. strigosa and S. siderea extracts, while the P. astreoides extract was more potent in human erythrocytes. Upon comparison with our previous study on the hemolytic properties of M. complanata aqueous extract [6], we found that P. strigosa extract was significantly more potent than M. complanata in both types of erythrocytes. These results suggest important differences between the hemolytic mechanisms of these reef-forming cnidarians.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The results obtained in this study showed that rat erythrocytes were more sensitive to P. strigosa and S. siderea extracts, while the P. astreoides extract was more potent in human erythrocytes. Upon comparison with our previous study on the hemolytic properties of M. complanata aqueous extract [6], we found that P. strigosa extract was significantly more potent than M. complanata in both types of erythrocytes. These results suggest important differences between the hemolytic mechanisms of these reef-forming cnidarians.…”
Section: Discussionsupporting
confidence: 51%
“…It is well-documented that the venomous content of nematocysts comprises mainly proteins and peptides such as enzymes, pore-forming components, and neurotoxins that specifically modulate several types of ion channels [3, 4]. Non-nematocystic toxins have also been found in cnidarian tissues [5, 6]; most of them are secondary metabolites that are usually released to their surroundings as antipredatory, antimicrobial, allelopathic, and antifouling agents [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Concerning cytolysins with PLA 2 activity, kinetic studies have revealed that these enzymes can display different affinities for membranes depending on the phospholipid composition [ 26 ]. In a previous study, regarding characterization of the hemolytic activity of the aqueous extract of M. complanata collected in the Mexican Caribbean, we found a similar behavior on the erythrocytes susceptibility to lysis [ 27 ], which suggests that cytolysins produced by both Caribbean hydrocorals have a high similarity in the membrane-binding domains. These results are in contrast with those found by Shiomi et al [ 9 ], who tested the hemolytic activity of M. dichotoma and M. platyphylla venoms on cow, horse, sheep, rabbit, guinea pig, mouse, and chicken erythrocytes.…”
Section: Discussionmentioning
confidence: 68%
“…There is abundant evidence from in vitro and in vivo studies which suggest that cndarian venoms from all classes in the phylum are heat labile (Table 4) [31,32,33,34,35,36,37,38,39,40,41,42,43,44,45]. Some have suggested that the mechanism by which heat provides pain relief is unrelated to inactivation of venom components.…”
Section: Mechanism Of Action Of Heat/hot-water Immersionmentioning
confidence: 99%